Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1210/en.2003-1049
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Postnatal Development of Testicular Steroidogenesis in Luteinizing Hormone Receptor Knockout Mice

Abstract: We recently demonstrated that the sexual development of LH receptor (LHR) knockout mice is normal until birth, but is totally arrested thereafter. To study further the functional defects of LHR knockout mice, the expression of selected Leydig cell-specific genes was studied in (-/-) and control (+/+) mice between birth and adulthood. Testis weights were similar at birth in both types of mice, but after about 3 wk, the (-/-) testes remained significantly lighter, weighing only 18% of (+/+) testes on d 70. Testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 44 publications
11
97
0
1
Order By: Relevance
“…The 8 week long testosterone replacement regimen started at the prepubertal age of 21 days to restore both anatomical abnormalities and accessory sex organ function in these hypogonadal LuRKO male mice. [163][164][165] Additionally, in some LuRKO mice testosterone replacement also induced severe inflammation in the coagulating glands, vasa deferentia, and epididymis. 162 Long-term administration of testosterone in Lobund-Wistar and Noble rat strains has been shown to induce invasive prostate adenocarcinomas.…”
Section: Mouse Models Of Prostatitismentioning
confidence: 99%
“…The 8 week long testosterone replacement regimen started at the prepubertal age of 21 days to restore both anatomical abnormalities and accessory sex organ function in these hypogonadal LuRKO male mice. [163][164][165] Additionally, in some LuRKO mice testosterone replacement also induced severe inflammation in the coagulating glands, vasa deferentia, and epididymis. 162 Long-term administration of testosterone in Lobund-Wistar and Noble rat strains has been shown to induce invasive prostate adenocarcinomas.…”
Section: Mouse Models Of Prostatitismentioning
confidence: 99%
“…In conclusion, poorly developed secondary sex characteristics and infertility are observed in both sexes. Further detail about the phenotype of this model are in our previous reports (Zhang et al, 2001a;Zhang et al, 2003;Zhang et al, 2004;Pakarainen et al, 2005c;Pakarainen et al, 2005b;Pakarainen et al, 2005a).…”
Section: Lh/hcg-r Knockout (Lurko) Micementioning
confidence: 99%
“…This work showed that Leydig cell regeneration after EDS is dependent on LH (Molenaar et al ., 1986; Sriraman et al ., 2003) although some early proliferation and differentiation appears to occur independent of LH (Teerds et al ., 1989). Subsequent studies have shown that similar control mechanisms regulate normal adult Leydig cell development at puberty (Clark et al ., 2000; Gnessi et al ., 2000; Baker & O'Shaughnessy, 2001; Zhang et al ., 2001, 2004; Baker et al ., 2003). Other factors such as DHH, PDGF and anti‐Müllerian hormone (AMH) have been implicated in the development of Leydig cells both during development and re‐generation (Salva et al ., 2004; Josso et al ., 2006; O'Shaughnessy et al ., 2008b) and further studies on EDS regeneration have also suggested that nerve growth factor (NGF) and Sertoli cells are involved in Leydig cell proliferation, differentiation and survival (Yan et al ., 2000; Zhang et al ., 2013).…”
Section: Leydig Cellsmentioning
confidence: 99%